Efektivitas Pelayanan Program Kartu Identitas Anak Dalam Meningkatkan Kesejahteraan Anak Di Kelurahan Wonokromo - Laduni, Rizki Revashandi Ihsan; Wibawani, Sri (UNIVERSITAS ISLAM SYEKH YUSUF, 2023)
In this era of increasing development, the needs and desires of society are becoming increasingly complex. Because one third of Indonesia's population is children. Therefore, the state must pay special attention to children and their role in the continuation of the country's development. One of the ways the government protects children is through their right to identity, therefore the government creates child privacy protection services through the Child Identification Card (KIA) program, especially aimed at children under the age of 17. The Child Identification Card (Kia) program, guarantees the protection of fair legal certainty and the right to equal treatment in the eyes of the law, including the collection of demographic information and provides a child's body identification card This card is intended to facilitate the acquisition of his or her site (Kia) This study aims to analyze the effectiveness of the child identification card project service in Wonokromo village. This research method uses a qualitative method using a descriptive method. Data were collected through interviews, observations, and documentation. This research discusses the theory of effectiveness. It consists of three indicators: goal achievement, integration, and adaptation. The results showed that the effectiveness of the Child Identity Document (IKD) program services in improving child welfare in Wonokromo Sub-district, Surabaya City was evidenced by three performance indicators that went well according to their designation.